Bibliometric analysis of dental adhesives: research status and frontier development - Hu, Xurui; Sun, Tao; Kuang, Bin; Sun, Yanyan; Chen, Lei; Ding, Huanyang (Frontiers in Materials, 2023)
Objective A visual analysis of the literature in the field of dental adhesives is conducted in order to explore the current state of research, cutting-edge areas of interest, and future development trends in this domain. Methods English literature related to dental adhesives published between 2000 and 2023 was searched in the Web of Science Core Collection database. The retrieved results were then imported into VOSviewer and CiteSpace software in plain text format. Various data, such as journal names, authors, institutions, countries, and keywords, were extracted for further bibliometric analysis. Results A total of 19,403 publications were retrieved, featuring 42,365 authors, 7,359 institutions, 121 countries, and 1,523 journals. The annual publication and cumulative publication rates in this field are both on the rise. Among them, DENTAL MATERIALS is the journal with the highest publication rate, cumulative publication rate, and number of citations. Ozcan M is the author with the most publications and within the limitations of this study, is considered an influential author in the field (with the highest intermediary centrality score) and Meerbeek B is the author with the highest number of citations. UNIV SAO PAULO is the institution with the highest publication rate. The United States is the country with the highest publication rate and has the most collaborative partnerships with other countries. Collaboration between different authors, institutions, and countries in this field is indeed close, which has greatly contributed to the rapid development of dental adhesives. Current research focuses on various aspects such as the types of dental adhesives, adhesive strength, dental diseases, and clinical trials. Future research directions mainly concentrate on aspects such as nanoparticles, 3D printing, universal adhesives, antibacterial properties of adhesives, and adhesive strength. Conclusions Within the defined scope of this study, we have conducted a quantitative and objective analysis of the current research status and emerging trends in dental adhesives. This analysis establishes a knowledge foundation and introduces novel perspectives for future in-depth investigations in this field.